Distribution patterns of lianas from subtropical to subboreal zones of the Japanese archipelago and the difference between climbing types - Gen Kusakabe; Hideki Mori; Tsutom Hiura (Basic and Applied Ecology, 2023)
Several factors related to liana abundance have been shown at broad scales, however, the information on factors affecting liana distribution in temperate zones is limited. Climbing types of lianas appear to be associated with interspecific variations of lianas and may be related to the broad-scale distribution and functions of lianas. We aimed to assess the environmental factors related to the abundance of all lianas and those of each climbing type from subtropical to subboreal forests in the Japanese archipelago to better understand the geographical gradient of the liana community.We established six 400 m2 subplots within each of 19 forest plots and recorded the species, stem diameter, and climbing types of lianas with stem diameters ≥ 1 cm. We used generalised linear mixed effects models and model selection based on Akaike's information criterion to examine the effects of climate, soil, and forest structural attributes on liana stem density and basal area.Liana abundance varied substantially among the 19 plots and some forests were characterized by abundant lianas in temperate zones. Twining and root climbers were the major climbing types. Mean annual temperature positively affected the stem density of twining climbers and negatively affected the basal area of root climbers. Maximum snow depth positively affected the stem density of root climbers and negatively affected the basal area of twining climbers. Carbon:nitrogen ratio and dry mass of the soil organic layer had negative effects on the abundance of twining climbers and stem density of both climbers, respectively. Tree basal area positively affected the basal area of root climbers.This study demonstrated the effects of environmental factors, including unique factors such as snow accumulation, on liana distribution at a broad scale from the subtropical to the subboreal zone. Furthermore, the difference between climbing types in distribution may contribute to the gradient of forest ecosystem functions along the environmental factors.